Banking against Global Economic Crisis: Comparison of Covid-19 Pandemic and 2008 Recession - Putri Andari Ferranti; Riska Rosdiana; Indra Raharja (Universitas Mercu Buana, 2023)
In the last twenty years, there has been two major global economic crises in Indonesia with very different origin, the 2008 global financial crisis was induced by failure of international banks while the 2020 global pandemic crisis was induced by economic slowdown due to worldwide infectious disease. Previous researches implied that the financial crisis had more tendency to deplete capital without slowing down credit distribution thus facing bigger risk of illiquidity while it had the opposite effect on the pandemic crisis where banks withhold their capital too much and distributed too little leading to less profitability. We found that the persistence of changes of CAR, LDR, NPL, and ROA as capital, liquidity, and profitability measures during both crises don’t differ significantly. Keywords: Banking, pandemic, economic crisis.